Study on phase transition phenomena in network traffic anomalies - WANG Xin 1; DING Li 2 (Tongxin xuebao)
Based on the theory of phase transition phenomena,the hypostases of network traffic anomalies with jam were researched.A new congestion mitigating mechanism with motional feedback of Hurst parameter was presented.Technical analysis and analog simulation were used to validate the feasible of the method and advantages over classical approach.It opens up new vista of research for this research direction.